On starlikeness of Libera transform - Nunokawa, Mamoru; Sokol, Janusz (Universiti Kebangsaan Malaysia, 2015)
Let A denote the class of functions f that are analytic in the unit disc D and normalized by f (0) = f ʹ(0) – 1 = 0. In this paper conditions are determined for starlikeness of the Libera integral of functions such that ⎪arg {f ʹ}⎪ < δ in D. The results of Miller and Mocanu (2002) on Libera transform of functions with bounded turning are improved.